Tuberculosis patient and family education through videography in El Salvador. (August 2016) - Wilson, John W.; Ramos, Julio Garay; Castillo, Francisco; F. Castellanos, Evelyn; Escalante, Patricio
Abstract: Background: Tublosis (TB) and the approaches to successful management are commonly misunderstood health topics among patients and family members within resource-limited settings. Such public misconceptions often result in delayed diagnoses of afflicted patients, suboptimal compliance with prescribed therapies and a negative community social stigma that hinders effective contact investigations. Objective: To determine through an observational field pilot study if videography-based TB education program can be implemented in busy resource-limited outpatient TB clinic settings and improve both patient and family understanding of TB and its treatment, as well as, improve the efficiency of TB medical evaluations and corresponding contact investigations. Methods: We produced and implemented a videography-based health educational pilot strategy in 14 TB clinics within El Salvador to supplement the discussions between health providers, patients and families. Field observations and impressions after the first year of implementation were recorded. Results: After viewing the video, patient impressions revealed greater understanding of TB including how it's transmitted and successfully treated, as well as, a more optimistic outlook of the diagnosis. Family members viewing the video displayed less fear and greater interest in TB and also exhibited more support for relatives undergoing evaluation or treatment. Salvadorian TB health providers reported improvements in patient compliance with treatment, contact investigations of suspected patients, delivery of sputum samples for testing, clinic time-efficiency spent with patients, and an observed reduction of negative family stigma of TB. Conclusions: Our findings suggest that videography-based TB education can be successfully implemented in busy and resource-limited outpatient settings, and can provide a potentially efficient and low-cost effective strategy towards optimizing patient understanding, acceptance and compliance with TB treatment recommendations. This feasibility pilot study provides an opportunity within underresourced clinics for further evaluation regarding the favorable educational and sustainable impact of videography-based health education.